2019
DOI: 10.1038/s41467-019-10337-3
|View full text |Cite
|
Sign up to set email alerts
|

The footprint of column collapse regimes on pyroclastic flow temperatures and plume heights

Abstract: The gravitational collapse of eruption columns generates ground-hugging pyroclastic density currents (PDCs) with highly variable temperatures, high enough to be a threat for communities surrounding volcanoes. The reasons for such great temperature variability are debated in terms of eruptive versus transport and emplacement processes. Here, using a three-dimensional multiphase model, we show that the initial temperature of PDCs linearly correlates to the percentage of collapsing mass, with a maximum temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…The boundary between a convective and collapsing column can be mapped out using PlumeRise, where the critical parameters controlling the fate of the column are gas mass fraction (volatile content of the magma), mass eruption rate (ṁ), and vent radius ( Table 1). Clarke (2020) found that by taking the initial parameters for, and assessing the height of the top of the gas thrust region (defined by local minima in plume velocity; e.g., Trolese et al, 2019) for columns at the convective-column/collapsing-column transition: H 0 at the onset of collapse can be estimated; given a vent radius and water content of the magma (Equation 2).…”
Section: Parameterizing Pdc Collapse Heightmentioning
confidence: 99%
“…The boundary between a convective and collapsing column can be mapped out using PlumeRise, where the critical parameters controlling the fate of the column are gas mass fraction (volatile content of the magma), mass eruption rate (ṁ), and vent radius ( Table 1). Clarke (2020) found that by taking the initial parameters for, and assessing the height of the top of the gas thrust region (defined by local minima in plume velocity; e.g., Trolese et al, 2019) for columns at the convective-column/collapsing-column transition: H 0 at the onset of collapse can be estimated; given a vent radius and water content of the magma (Equation 2).…”
Section: Parameterizing Pdc Collapse Heightmentioning
confidence: 99%
“…To reconstruct the mass eruption rate at the time of collapse during transitional regimes, we have assumed, based on Wilson et al (1980), that this is equal to the maximum intensity achieved during the convective phase. However, the numerical investigations of Trolese et al (2019) demonstrate that plume height is strongly reduced during partial collapse episodes, so that the mass eruption rate might be underestimated. Moreover, in some situations full collapse (boiling over or fountain collapse; Fisher and Heiken 1982;Druitt et al 2002a;Sulpizio et al 2014) of a subplinian column can be triggered by the downward collapse of the edifice into an emptying chamber to form a summit caldera.…”
Section: Subplinian Eruption Modelling and Hazard Assessmentmentioning
confidence: 99%
“…During collapse regimes, the eruptive mixture at the time of collapse can be relatively dilute, especially in oscillating columns where it can have an average density as low as~10 kg/m 3 , i.e. a particle volume concentration of less than~10 −2 (Wilson et al 1980;Woods 1988;Neri and Dobran 1994;Esposti Ongaro et al 2002, 2008aSuzuki and Koyaguchi 2012;Trolese et al 2019). Nonetheless, PDCs manifest a steep vertical stratification in the proximal region around the vent, where breccias are often observed (Branney and Kokelaar 2002;Valentine and Sweeney 2018).…”
Section: Modelling Of Pdc Dynamics and Hazardmentioning
confidence: 99%
“…Finally, PVHA is often solely seen as an end product while it should also be considered a driver for research. If epistemic uncertainties are comprehensively quantified and ranked (e.g., Stefanescu et al, 2012a,b;Rougier and Beven, 2013;Spiller et al, 2014;Tierz et al, 2016a), then sensitivity of PVHA outputs can be explicitly explored (e.g., Tierz et al, 2016a;Bevilacqua et al, 2017;Sandri et al, 2018), and data collection can be aimed at reducing the overall uncertainty to improve volcanic hazard assessment (e.g., Tierz et al, 2016a;Trolese et al, 2019). The above example of PVHA of PDCs at the metropolitan area of Napoli exemplifies how research can focus on the most critical, volcano-specific aspects linked to PDC hazard: e.g., spatial probability of vent opening at Campi Flegrei and probability of eruption size at Somma-Vesuvius.…”
Section: Misconceptions Around Pvhamentioning
confidence: 99%